Copper Adsorption as Affected by Electrolyte Concentration and Sodium Adsorption Ratio in Three Major Soil Series in Sudan - Elamin, E A; Hussein, A H (Annals of Arid Zone, 2016)
The irrigated soils of the Sudan Gezira (about 925,000 ha) produce the greater share of cotton in the Sudan and coillribute significantly in the production of wheat, sorghum and ground nut. In the northern part of the Gezira the soils are generally saline-sodic. Despite the well-known importance of copper in crop production, very little is known about the effects of salinity and sodicity on its adsorption in soil. This work was undertaken to investigate the effects of electrolyte concentration (C) and sodium adsorption ratio (SAR) on copper adsorption. Copper retention decreased as electrolyte concentration increased, with maximum adsorption occurring at low electrolyte concentration having high pH and high negative charge. SAR had little effect on. Cu adsorption as precipitation prevailed at high pH. It was found that the adsorption capacity of the three soils was similar, despite the variation in CaC03 and clay contents, and hence the cation exchange capacity. Copper was more soluble in the saline phases of the Gezira soils, whereas sodicity had little effect.